Crystal structures of human glyoxalase I and its complex with TLSC702 reveal inhibitor binding mode and substrate preference. Issue 11 (8th April 2022) - Usami, Midori; Ando, Koki; Shibuya, Asuka; Takasawa, Ryoko; Yokoyama, Hideshi
Abstract : Human glyoxalase I (hGLO I) is an enzyme for detoxification of methylglyoxal (MG) and has been considered an attractive target for the development of new anticancer drugs. In our previous report, the GLO I inhibitor TLSC702 induced apoptosis in tumor cells. Here, we determined the crystal structures of hGLO I and its complex with TLSC702. In the complex, the carboxyl O atom of TLSC702 is coordinated to Zn 2+, and TLSC702 mainly shows van der Waals interaction with hydrophobic residues. In the inhibitor‐unbound structure, glycerol, which has similar functional groups to MG, was bound to Zn 2+, indicating that GLO I can easily bind to MG. This study provides a structural basis to develop better anticancer drugs. Abstract : Human glyoxalase I (hGLO I) is a zinc metalloenzyme for detoxification of methylglyoxal (MG), and it is an attractive target for the development of new anticancer drugs. Crystal structures of hGLO I provided insights into the binding mode of its inhibitor TLSC702 and showed that glycerol, which has similar functional groups to MG, can bind to zinc.